The Shifting Meaning of Walīmatul ‘Urs in the Era of Society 5.0 in Indonesia: Islamic Law Perspective - Syufa'at, Syufa'at; Muchimah, Muchimah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
The advent of globalization, ushering in the era of Society 5.0, has turned marriage events into a focal point of cultural dynamics. An example of this is evident in the celebration of weddings, known as walīmatul ‘urs. This study delves into the walīmatul ‘urs festivities organized by various Muslim celebrities in Indonesia. While these celebrities uphold the Islamic marital contract, they also hold extravagant wedding ceremonies infused with Western-inspired themes that come with significant costs. This study is a qualitative phenomenological study with an approach to Islamic law. This study analyzes media content to get an overview of the phenomenon of marriage among celebrities. The data collection process uses three techniques: observation, interviews from digital sources, and documentation. This study concludes that the purpose and main meaning of walīmatul ‘urs according to Islamic family law is as a sacred and strong bond (mithāqan ghalīdhan), a form of expression of gratitude to God and happiness in addition to providing benefits to society. The meaning of walimatul 'urs then underwent a shift in essence in the context of Indonesian Muslim celebrities, which were partly influenced by technological advances in the Society 5.0 era. Open (explicit) and implicit transformations and shifts in interpretation, when walimatul 'urs develops into a symbolic representation of social status, which is often characterized by luxury and functions as a venue to elevate one's social status.